Laboratory markers used to predict mortality in severe COVID-19 - Bindal , Ahmet; Patmano , Mehmet; Cansun , Funda (Annals of Medical Research, 2022)
Aim: Herein, we aimed to examine the laboratory parameters of COVID-19 patients and differentiate the parameters that can be used in mortality prediction. Material and Methods: The study retrospectively examined the patients who needed intensive care unit due to COVID-19 between March 2020 and December 2020. Three hundred and seventy-four patients who met the study criteria were included in the study. Two main groups were formed: patients discharged from the intensive care unit with no mortality and patients with a mortal course. Patients discharged constituted Group- 1, and patients who died constituted Group- 2. Patients were examined regarding demographic features, clinical, and laboratory characteristics. Results: Group- 1 consisted of survived patients (n=148, 39.5%), while Group- 2 patients were the patients with mortal course (n=226, 60.4%). In Group-1, 84 (56.8%) of the patients were male, while in Group-2, 127 (56.2%) were male. In the mortality group, procalcitonin, CRP, BUN, D-dimer, troponin, LDH, lactate, and INR values were significantly higher, albumin value was lower (p< 0.001). PLT and D-dimer were found as independent variables of mortality according to the logistic regression analysis. Conclusion: High procalcitonin and D-dimer values obtained with routinely examined rapid and easily accessible blood tests of COVID-19 patients may contribute to mortality prediction.